STUDI PENAMBATAN MOLEKUL SENYAWA METABOLIT SEKUNDER EKSTRAK AKAR TAWAR SERIBU (Bauhinia purpurea L) SEBAGAI POTENSI INHIBITOR α-Glukosidase - Nurul Fajeriyati; Rizka Mulya Miranti; Yulianita Pratiwi Indah Lestari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Diabetes mellitus is a disease characterized by elevated blood glucose levels due to impaired insulin secretion or action. A therapeutic development strategy involves inhibiting the α-glucosidase enzyme. Bauhinia purpurea, L. is known to contain various compounds with potential antidiabetic activity. This study aims to investigate the potential of secondary metabolites from Bauhinia purpurea, L. extract as α-glucosidase inhibitors using an in silico molecular docking approach and ADMET prediction. Test compounds were obtained from LC-MS identification results, and their three-dimensional structures were downloaded from the PubChem database. The protein structure was obtained from the Protein Data Bank (PDB ID: 3L4W). The molecular docking process utilized the AutoDock Tools software, yielding a validation result of 1.9 Å. The results showed ΔG values ranging from -4.00 kcal/mol to -8.26 kcal/mol. ADMET prediction results indicated high HIA values >90%, Caco2 permeability in the low permeability category (<4 nm·s⁻¹), low BBB values, and AMES test results classified as non-mutagenic for all test compounds. Based on these results, the secondary metabolites contained in the Bauhinia purpurea, L. extract show potential as α-glucosidase inhibitors with favorable pharmacokinetic parameters, making them suitable for development into drug candidates through pharmaceutical or chemical structural modifications.